20 Elite upland breeding lines out-yielding NERICA 4 by up to 57% identified in Cote d'Ivoire. - CGIAR Research Program on Rice (2020)
20 elite upland breeding lines out-yielding check variety NERICA 4 by 12-57% were identified in yield trials conducted at Mbe, Cote d'Ivoire.